Formatting Culture. The Mpeg group and the technoscientific innovation by digital formats - Leonardo Chiariglione; Paolo Magaudda (Tecnoscienza, 2013)
This conversation reconstructs the process of technoscientific innovation of digital formats pursued in the ‘80s by the MPEG group led by Leonardo Chiariglione. Through a historical and cultural frame provided by Paolo Magaudda and the very words of the main character of this technoscientific story, Leonardo Chiariglione, the contribution gives fresh insights into the relationship between sociotechnical standards and the digitization of media culture.